Corporate Culture and Employee Generation Gap in the Era of Disruption: A Case Study at PT. PLN Bali Distribution - Marsudi, Erlinda Dwi Cahyani; Sanica, I Gede (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2021)
In facing the era of disruption, change management is not enough, but presenting sustaining innovation has become a major obligation for the company. Disruption has penetrated all sides of world life, especially in corporate culture. On the other hand, the era of disruption also greatly impacts every employee, especially with the presence of intergenerational gaps in company employees. This study aims to determine the extent to which corporate culture and the role of the company face the generation gap in the era of disruption. The research method used is a qualitative research method with data collection techniques done by triangulation using observation, interviews and documentation. Through the technical analysis of Miles and Huberman, it was found that there were a number of challenges faced in the era of disruption and corporate culture in synergy with strategies to face challenges with several key steps, namely: promoting the culture of SIPP (mutual trust, integrity, caring, and learning), code of conduct (COC) the company PT PLN Distribution Bali, and the COC in the field to minimize employee gaps. It can be concluded that organizational culture plays an important role in achieving company targets so that by upholding the concept of corporate culture it can minimize the gaps that exist in the company in the world of the era of disruption.